The relationship between enterprise architecture and business modeling – Impact in benefit realization - Kangas, Niko (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Contemporary business environment has become complex and turbulent. Conventional business logic and strategic approaches cannot answer to unseen challenges that the digitalization of business environment has brought. For organizations to cope with the challenging environment, enterprise architecture (EA) has been deemed as a solution. However, even though scientific literature forecasts ample benefits after successful engagement in EA, few organizations have consistent EA activities. Additionally, business modeling (BM) is another relatively new approach to cope with demanding environment. The high level concepts of EA and BM are straightforward to relate, but the interconnection of the two is still under research by both communities. The purpose of this thesis is to verify current theories of EA and BM benefits, consistency in IT investments, and their impact in benefit realization. This study relies on quantitative research methods by conducting descriptive and frequency analyses on selected secondary data. The results are consistent with the reviewed literature, suggesting that engaging consistently in EA and BM activities, and having a clear strategy in IT investments result in improved organizational benefit realization. In general, the results confirm the positive relationship of consistent EA work and benefit realization. However, the results also verify that even though the EA approach was proposed approximately 30 years ago, it is still having difficulties in finding a strong foothold in organizations. Out of 181 respondents, only 13 had a consistent EA approach in use. This also underlines the weakness of the results: after sanity check the data sample proved to be statistically too small to produce strong generalizations.